Tadrīs Mahārah al-Istimā’ Ligahiri an-Nāţiqīna Bi al-‘Arabiyyah Min Khilāli Kitābi Silisilati Ta’līmi al-Lughah al-‘Arabiyyah - Fajar Rachmadhani (University of Darussalam Gontor, 2019)
Tadrīs Mahārah al-Istimā’ Ligahiri an-Nāţiqīna Bi al-‘Arabiyyah Min Khilāli Kitābi Silisilati Ta’līmi al-Lughah al-‘ArabiyyahFajar RachmadhaniUniversitas Muhammadiyah Yogyakartafajarrachmadhani@umy.ac.idAbstractThe listening skill is the first and most important skill the child experiences in acquiring the mother tongue. The child starts his external relationship with him through listening. It is known that the skill of listening is necessary in human life, because it is the means of communication between people in the way of earning vocabulary, and learn the types of sentences and structures, knowledge of ideas and concepts, etc., the prerequisite for this skill is the ability of the listener to distinguish audible voices. It is true that a student may read and write in a foreign language without improving the communicative aspect of hearing comprehension and speech, but he remains unable to use the language correctly. In addition, the method of teaching listening skills to students, especially non-Arabic speakers, is more important than the listening skill itself, so that the method is more important than the material. Therefore, the teachers of Arabic language for non-native speakers must pay attention to the attention during their teaching of great interest. This research discusses the role of listening skill and teaching method for non-Arabic speakers through the book of the series of Arabic language instruction issued by Imam Muhammad bin Saud Islamic University in Saudi Arabia, so that this book is taught in various universities and institutes of Arabic language teaching in Indonesia.Keywords: Mahārah al-Istimā’, Tadrīs al-Lughah, Kitāb Silsilahتدريس مهارة الاستماع لغير الناطقين بالعربية من خلال كتاب